Tuberculosis among foreign-born residents of southern Florida, 1995 - Granich, R M; Zuber, P L; McMillan, M; Cobb, J D; Burr, J; Sfakianaki, E D; Fussell, M; Binkin, N J (Public health reports (1974), 1998)
To examine the characteristics of foreign-born people with tuberculosis (TB) in Southern Florida, their contribution to the total number of TB cases, and available data on their HIV status as well as to determine the number of cases detected by the overseas medical screening of immigrants and refugees. The authors reviewed TB cases reported by Broward, Dade, and Palm Beach counties in 1995. Case records were matched against the CDC Division of Quarantine database of immigrants and refugees suspected to have TB at the time of visa application overseas. Nearly half (49%) of TB cases in the three counties were among people born outside the United States--34% in Broward County, 58% in Dade County, and 40% in Palm Beach County. A high percentage (26%) were co-infected with HIV. Of those with known date of arrival, 68% had been in the United States for five or more years. Only three cases had been identified by overseas immigrant screening. A low percentage of TB cases in foreign-born people were identified through the overseas screening system. Controlling TB in South Florida will require efforts targeted toward high risk populations, including people with HIV infection.